Impact of non-performing loans on financial performance: A case of Sri Lankan listed commercial banks - Jathurika, M. (Faculty of Management Studies & Commerce, University of Jaffna, 2019)
The purpose of this investigation is to extend earlier research on the impact of Non- Performing Loans on financial performance. The study confines only nine listed commercial banks in Sri Lanka through the purposive sampling due to the minimize of missing data and links secondary data derived from the annual financial reports of commercial banks using the CSE’s database. The analysed non-performing loans indicator include non-performing loan ratio while financial performance indicator incudes return on assets, return on equity. Regression and Correlation analysis have been employed for the study to investigate the effects of non-performing loans on financial performance. The results of the analysis have revealed that attribute of Non- Performing Loans which is Non-Performing Loan ratio have a negative and significant impact on Financial Performance. The prominent finding of the research utterly reveals that, non-performing loans significantly influences the financial performance of listed commercial banks in Sri Lanka with the negative relationship. Based on the Finding, researcher recommends banks to devise new strategies and implement effective policies relating with management of non-performing loans to improve their financial viability as non-performing loans is one of the significant factors that determine the financial performance which this study concluded. Thus this study will be useful for the management personnel of banks to create the ideas for protect banks from crisis and enhance the performance of banks.
Keywords: Non-performing loans; financial performance; listed commercial banks